Generating tank pressurization launch vehicle with RP-1 - Мітіков, Юрій Олексійович (Eastern-European Journal of Enterprise Technologies, 2012)
The study of high-generator pressurization system booster tank with RP-1 was done. Optimum operating conditions are given